2020
DOI: 10.1111/jne.12850
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin ameliorates maternal separation‐induced ultrasonic vocalisation calls in mouse pups prenatally exposed to valproic acid

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder estimated by the World Health Organization to occur in one of 160 children worldwide. No pharmaceutical treatments are available to improve the deficits in social communication that are common symptoms of ASD. Recent clinical trials have focused on the nasal application of oxytocin, a neuronal peptide known to regulate a variety of social behaviours. However, the effect of oxytocin on this deficit is inconclusive. By contrast, evidence from ASD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…We found that prenatal OXTR deficiency induces many social deficits in offspring, it mimics the effects of maternal diabetes-induced anxiety-like behavior and ultrasonic vocalization ( Tsuji et al, 2020 ), while has little effect on ALB. Very interestingly, prenatal OXTR deficiency potentiates maternal diabetes-mediated anxiety-like behavior while again having little effect on ALB, which is consistent with previous findings that OXT is associated with anxiety, but not necessarily with ALB ( Yoshida et al, 2009 ; Puglia et al, 2015 , 2018 ; Duque-Wilckens et al, 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…We found that prenatal OXTR deficiency induces many social deficits in offspring, it mimics the effects of maternal diabetes-induced anxiety-like behavior and ultrasonic vocalization ( Tsuji et al, 2020 ), while has little effect on ALB. Very interestingly, prenatal OXTR deficiency potentiates maternal diabetes-mediated anxiety-like behavior while again having little effect on ALB, which is consistent with previous findings that OXT is associated with anxiety, but not necessarily with ALB ( Yoshida et al, 2009 ; Puglia et al, 2015 , 2018 ; Duque-Wilckens et al, 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…Valproic acid administration to pregnant rats and mice during gestation leads to autistic-like symptoms in the offspring, and this method is widely used as an animal model for autism ( Morales-Navas et al, 2020 ; Tsuji et al, 2020 ). USVs can be observed during the neonatal period, as these isolation-induced calls serve to elicit retrieval behavior from lactating mice ( Gzielo et al, 2020 ); thus, they may serve as communication signals between the mother and pups.…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the modulatory effect that testosterone and oxytocin have on USV production. [39][40][41][42][43][44][45] Importantly, the neuronal circuitry underlying USVs has recently been identified and is being studied extensively. 20,25,[46][47][48][49][50][51][52][53] Because of their social and affective significance and our growing mechanistic understanding, mouse USVs are increasingly being used as a behavioral measure in neurodevelopmental and neurolinguistic translational research.…”
Section: Introductionmentioning
confidence: 99%